Pengembangan Media Pembelajaran Flipbook Interaktif PMRI Berbasis Youtube untuk Meningkatkan Daya Tarik Siswa - Dwi Yulianto (PT FORMOSA CENDEKIA GLOBAL, 2022)
The lack of use of learning media in learning makes students less enthusiastic in participating in learning. In learning students also need learning media that can help understand the material repeatedly so that it is necessary to develop learning media such as interactive youtube-based flipbook electronic teaching materials. This study aims to produce interactive flipbook electronic teaching materials based on the SPLDV class VIII material which have been tested for validity and reliability. This research is a development research using the ADDIE model. The subjects in this study were: 2 material experts, 2 media experts and 30 student responses. The data collection method used an instrument in the form of a rating scale with a validity assessment sheet for interactive flipbook electronic teaching materials based on SPLDV material. The data analysis technique used is qualitative analysis and quantitative analysis. The data were analyzed using the mean formula to obtain the average score. The results of the research obtained are interactive flipbook electronic teaching materials based on YouTube, SPLDV material received an assessment of 85.50% from media experts, 85.83% from material experts, and 85.73% from users or students. So it can be concluded that the interactive flipbook electronic teaching material based on the SPLDV YouTube material is very feasible at MTs Kun Karima.